2009
DOI: 10.3319/tao.2008.01.14.01(f3c)
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the Climate Monitoring Utility of Radio Occultation Data: From CHAMP to FORMOSAT-3/COSMIC

Abstract: AB STRACTRa dio Occultation (RO) data, us ing Global Po si tion ing Sys tem (GPS) sig nals, de liver high qual ity ob ser va tions of the at mo sphere, which are well suited for mon i tor ing global cli mate change. The spe cial cli mate util ity of RO data arises from their ac cu racy and long-term sta bil ity due to self-cal i bra tion. Launched in 2000, the Ger man re search sat el lite CHAMP (CHAl leng ing Minisatellite Pay load for geoscientific re search) pro vides the first op por tu nity to cre ate RO … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
47
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 57 publications
(50 citation statements)
references
References 36 publications
3
47
0
Order By: Relevance
“…However, the characteristic differences between 2005 and 2006 do not change significantly against the top-row panels, indicating that introducing an additional GPSRO mission (F3C) to the RO data set is not changing its behavior substantially. This consistency of GPSRO data from different missions has been demonstrated in several studies (Foelsche et al, 2009Steiner et al, 2011).…”
Section: Change In Temperature Difference Characteristics In 2005/06supporting
confidence: 70%
“…However, the characteristic differences between 2005 and 2006 do not change significantly against the top-row panels, indicating that introducing an additional GPSRO mission (F3C) to the RO data set is not changing its behavior substantially. This consistency of GPSRO data from different missions has been demonstrated in several studies (Foelsche et al, 2009Steiner et al, 2011).…”
Section: Change In Temperature Difference Characteristics In 2005/06supporting
confidence: 70%
“…The mean temperature difference between the collocated soundings of COSMIC (Constellation Observing System for Meteorology, Ionosphere, and Climate) and CHAMP was within 0.1 K from 200 to 20 hPa (Ho et al, 2009b;Anthes et al, 2008;Foelsche et al, 2009). At 20 hPa, the mean temperature difference between COSMIC and CHAMP was within 0.05 K (Ho et al, 2009b).…”
Section: Introductionmentioning
confidence: 93%
“…A number of studies confirmed the capability of RO measurements to monitor the dry atmosphere (above around 8 km; Foelsche et al, 2008Foelsche et al, , 2009) and for climate change detection (Leroy et al, 2006;Ho et al, 2009;Steiner et al, 2011;Ho et al, 2012). RO data feature inherent high accuracy and precision, high vertical resolution (100 to 200 m), all-weather capability, and long-term stability (Anthes, 2011), making them highly valuable for studying a large number of atmospheric phenomena.…”
Section: Introductionmentioning
confidence: 94%